Cassius Dio's forgotten history of early Rome : the "Roman history", Books 1-21 - Burden-Strevens, Christopher; Lindholmer, Mads (Historiography of Rome and Its Empire, 2019)
In a radical change of approach, Cassius Dio's Forgotten History of Early Rome illuminates the least explored and understood part of Cassius Dio's enormous Roman History : the first two decads, which span over half a millennium of history and constitute a quarter of Dio's work. Combining literary and historiographical perspectives with source-criticism and textual analysis for the first time in the study of Dio's early books, this collection of chapters demonstrates the integral place of 'early Rome' within the text as a whole and Dio's distinctive approach to this semi-mythical period. By focussing on these hitherto neglected portions of the text, this volume seeks to further the ongoing reappraisal of one of Rome's most significant but traditionally under-appreciated historians.